Analysis of Factors Affecting Migrant Worker Remittance in Denpasar City - Cokorda Gede Agung Deo Sukma Prawira; Made Dwi Setyadhi Mustika (International Journal of Economics, Commerce, and Management, 2024)
Two big problems generally faced by developing countries like Indonesia are low human development which leads to prosperity and economic inequality or inequality in the distribution of income between high-income groups and low-income groups. Migrants can increase family income in the area of origin thereby creating prosperity for the family and the area of origin through remittances sent by migrants from the migration area. This study aims to analyze the direct influence of education level, length of service, marital status, family responsibilities on the income and remittances of migrant workers in Denpasar City and the indirect influence of education level, length of service, marital status and family responsibilities on remittances through the income of migrant workers in the City Denpasar. The sample used in this research was 100 migrant workers in Denpasar City. This research uses a probability sampling method. The analysis techniques used are descriptive analysis and path analysis. The research results obtained state that education level, length of service, marital status and family responsibilities have a direct, positive and significant effect on the income of migrant workers in Denpasar City. Education level, length of service, marital status, family responsibilities and income have a direct positive and significant effect on remittances by migrant workers in Denpasar City. Education level, length of service, marital status and family responsibilities have an indirect effect on remittances through the income of migrant workers in Denpasar City.